2015
DOI: 10.18632/oncotarget.6330
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of isolated circulating tumor cells and tissue biopsies using whole-genome sequencing in prostate cancer

Abstract: Previous studies have demonstrated focal but limited molecular similarities between circulating tumor cells (CTCs) and biopsies using isolated genetic assays. We hypothesized that molecular similarity between CTCs and tissue exists at the single cell level when characterized by whole genome sequencing (WGS). By combining the NanoVelcro CTC Chip with laser capture microdissection (LCM), we developed a platform for single-CTC WGS. We performed this procedure on CTCs and tissue samples from a patient with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 55 publications
2
81
0
Order By: Relevance
“…Thus, we found that complex and heterogeneous drug resistance mechanisms exist in advanced prostate cancer, as revealed by the study of heterogeneous populations of CTCs. The degree of heterogeneity observed in CTCs in CRPC patients is consistent with intratumoral heterogeneity observed in patients with advanced metastatic prostate cancer, suggestive of the polyclonal seeding of divergent clones (Lohr et al 2014; Gundem et al 2015; Jiang et al 2015), and is reflective of the variety of molecular alterations that may occur in parallel in tumor cells during disease progression and the development of resistance to therapy.…”
Section: Insights Into Intratumoural Heterogeneity Through Ctcssupporting
confidence: 69%
“…Thus, we found that complex and heterogeneous drug resistance mechanisms exist in advanced prostate cancer, as revealed by the study of heterogeneous populations of CTCs. The degree of heterogeneity observed in CTCs in CRPC patients is consistent with intratumoral heterogeneity observed in patients with advanced metastatic prostate cancer, suggestive of the polyclonal seeding of divergent clones (Lohr et al 2014; Gundem et al 2015; Jiang et al 2015), and is reflective of the variety of molecular alterations that may occur in parallel in tumor cells during disease progression and the development of resistance to therapy.…”
Section: Insights Into Intratumoural Heterogeneity Through Ctcssupporting
confidence: 69%
“…These studies include that by De Luca et al, in which inter- and intra-patient heterogeneity is observed in the mutational status of breast cancer CTCs analysed by NGS [101]. In addition, there have been studies comparing CTCs and metastases or primary tumours at the single-cell level, such as the study performed by Jiang et al in which they discovered highly heterogeneous short structural variants of PTEN, RB1, and BRCA2 in all tumour and CTC prostate samples assessed using high-quality WGS [102]. Interestingly, Powell et al performed one of the first studies in CTCs focused on single-cell transcriptomes.…”
Section: Methods For Studying Tumour Heterogeneitymentioning
confidence: 99%
“…128,150 Recently, a modified assay has been reported, which consists of pre-labelling a RBC lysed blood sample with biotinylated Abs and recovering the labeled cells with the streptavidin-coated device. 52,148 Cell line recoveries were shown to be 65–93% depending on EpCAM expression (Table 1). 148 …”
Section: Microfluidic-based Biological Ctc Selectionmentioning
confidence: 99%